Calcium channels blocked activity: Providing the basis for medicinal use of Abies pindrow in diarrhea and bronchitis - Mushtaq, Sohaib; Chaudhry, Mueen Ahmad; Rahman, Hafiz Muhammad Abdul (Bangladesh Journal of Pharmacology, 2015)
Abies pindrow is widely used in traditional practice for the treatment of diarrhea and bronchitis and the present study was designed to validate its folkloric uses. The crude extract of A. pindrow inhibit spontaneously contracting (1-10 mg/mL) and high K+ (80 mM)-induced pre-contracted rabbit jejunum (3 mg/mL) in concentration dependent manner. A rightward shift in Ca+2 concentration response curves was seen in the presence of crude extract (0.1-0.3), similar to verapamil. In isolated tracheal tissue, A. pindrow inhibited, high K+ and carbachol (1 µM)-induced contractions, at 3 mg/mL and 10 mg/mL respectively, similar to that caused by verapamil. These results indicate the presence of calcium channels blocked activity in crude extract of A. pindrow, which provide sound basis for medicinal uses of A. pindrow in diarrhea and bronchitis.